Market Research and the Land Grant/USDA Communicator - Ned Browning (Journal of Applied Communications, 1987)
The word " marketing" evokes a variety of meanings. Sales, advertising, and publicity are just a few terms used synonymously. However, marketing, in the contemporary sense, is much more. It is a total systems approach to an organization's relationship with its constitutents, whether they be customers or the taxpaying public.